1996
DOI: 10.1210/mend.10.4.8721979
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for redundancy in propeptide/prohormone convertase activities in processing proglucagon: an antisense study.

Abstract: To further examine the physiological roles of the neuroendocrine prohormone convertases (PCs) in proglucagon processing, alpha TC1-6 cells were transiently transfected with PC1/3 and PC2 expression vectors containing either antisense or sense encoding cDNAs. PC1/3- and PC2-directed RIAs were used to determine that the PC1/3 antisense transfections lowered endogenous levels of PC1/3 by 40 +/- 7.9% but did not alter the levels of PC2. The PC2 antisense transfections decreased the endogenous levels of PC2 by 91 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…There is no detectable production of glucagon, oxyntomodulin, GLP-1, or other smaller processing products. Although other investigators have raised questions as to whether PC2 acting alone is capable of cleaving glucagon from proglucagon, especially cleavage at the N terminus of the glucagon sequence in the precursor (20,21), these results indicate that the action of another convertase is not likely. If another convertase were required for cleavage after GRPP (see Fig.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…There is no detectable production of glucagon, oxyntomodulin, GLP-1, or other smaller processing products. Although other investigators have raised questions as to whether PC2 acting alone is capable of cleaving glucagon from proglucagon, especially cleavage at the N terminus of the glucagon sequence in the precursor (20,21), these results indicate that the action of another convertase is not likely. If another convertase were required for cleavage after GRPP (see Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Proglucagon processing has been examined in a number of cell lines expressing PC2, PC3, or both convertases with proglucagon by coexpression techniques, and these studies have suggested that PC2 generates the A-cell-processing phenotype (12,13). However, other investigators have reported that PC2 acting alone is not able to generate mature glucagon (20,21). Some of these discrepancies may have arisen because of low levels of expression of PC2 obtained in transfection experiments or low levels of activity in partially purified preparations of the recombinant enzyme used for in vitro studies.…”
mentioning
confidence: 99%
“…Indeed, PC1/3 and PC2 cleave pro-opiomelanocortin at distinct pairs of basic residues in established cell lines (19) and in a temporal order in the corticotrophs (20). Specific patterns of cleavage by either PC1/3 or PC2 have also been demonstrated for proglucagon (21)(22)(23), proneurotensin (24), pro-thyrotropin-releasing hormone (25), proenkephalin (26,27), and procholecystokinin (28,29). The functional relevance of the proconvertases in a whole animal model was recently established by disrupting the corresponding genes such as these encoding PC2 (30) and PC4 (16).…”
mentioning
confidence: 97%
“…SPC2 is also expressed at high levels in the islet alpha cells, where it selectively processes proglucagon to liberate only glucagon as the major active hormone from this large multihormone precursor (19). On the other hand, in the neuroendocrine L cells of the gut, proglucagon is processed at different sites by SPC3 to liberate mainly two glucagon-like peptides-GLP1 and GLP2 (20)(21)(22). GLP1 enhances insulin secretion from the beta cells in response to glucose, whereas glucagon counters the hypoglycemic action of insulin by triggering hepatic glycogenolysis and enhancing hepatic gluconeogenesis to raise blood glucose levels (23)(24)(25).…”
mentioning
confidence: 99%